Overview Of Small Medium Businesses Case Study : Sungai Penuh City Jambi Province - Zefri Efdison; Murniati (CV. Inara, 2021)
This study aims to provide information and a map of the geographic potential of small industries in Sungai Penuh City, so that they can be a reference for all parties in seeing and developing the potential of small industries. The benefit of this research is as a material for consideration to determine the steps taken by small industries in dealing with their problems. The study was conducted on Small and Medium Enterprises/SMEs as many as 439 respondents/sample from 8,108 SMEs that are not registered with the Department of Industry and Cooperatives of Sungai Penuh City. Respondents are leaders or managers, consultants and consumers as information material about the real condition of small industries. This study uses survey methods and descriptive studies that aim to explain aspects that are relevant to the observed phenomena and offer problem ideas for further testing or research. The results of the Mapping of the Geographical Potential of Small Industries/MSMEs in Sungai City are 8,018 MSMEs. Based on the characteristics of the respondents, it shows that the business fields are varied and centrally located. The average workforce is low in elementary and junior high school education and its existence is not continuous, the average worker lacks previous experience. In terms of capital, generally own capital is not debt to the bank. While the raw materials used are mostly from outside the region. The marketing area is still limited to the surrounding area, promotion is still lacking, the tendency is that small industry owners and sellers are satisfied when the product is sold. In general, small industries have a high level of self-confidence and independence, only because of limited knowledge, small industries develop rather slowly. Product design tends to change, only imitates what is already on the market, lacks innovation, lacks creativity, only because of limited knowledge, small industries develop rather slowly.